Commutative algebra and noncommutative algebraic geometry - Eisenbud, david; Iyengar, Srikanth B.; Singh, Anurag K.; Stafford, J. Toby; Bergh, Michel Van den (New York, NY : Cambridge University Press, 2015)
This book surveys fundamental current topics in these two areas of research, with an emphasis on the lively interaction between them.
Volume II. Research Articles.
Includes bibliographical references and index.
Keywords: Commutative algebra; Algebraic Geometry